Does tumor rupture during robot-assisted partial nephrectomy have an impact on mid-term tumor recurrences? - Hawlina, Simon (Radiology and oncology (Ljubljana), 2023)
Background: Intraoperative kidney tumor rupture (TR) can occur during robot-assisted partial nephrectomy (RAPN) in daily clinical practice, but there are no solid guidelines on the management and implications of it. The purpose of the study was to investigate the impact of TR on tumor recurrences, what a surgeon should do if this adverse event occurs, and how to avoid it. Patients and methods: We retrospectively analyzed the first 100 patients who underwent RAPN at University Medical Centre Ljubljana, between 2018 and 2021. Patients were stratified into 2 groups (TR and no-TR) and were compared according to patient, tumor, pathologic, perioperative and postoperative characteristics and tumor recurrences, using the Mann-Whitney U test and chi-squared test. Results: Of the 100 patients, 14 had TR (14%); this occurred in tumors with higher RENAL nephrometry scores (P = 0.028) and mostly with papillary renal cell carcinomas (P = 0.043). Median warm ischemia time was longer for the TR group (22 vs. 15 min, P = 0.026). In terms of studied outcomes, there were no cases of local or distant recurrence after a median observation time of 39 months (interquartile range, 31-47 months) in both groups. We observed positive surgical margins on the final oncologic report in one case in the no-TR group. Conclusions: Tumor rupture during RAPN seems to be of no mid-term oncologic importance. According to presented results, we would recommend surgeons to proceed with tumor resection if this event occurs and abstain from conversion to radical nephrectomy or open partial nephrectomy. However, more similar cases should be studied to make more solid conclusions.
Keywords: čas tople ishemije; enucleation; enukleacija; karcinom ledvičnih celic; ponovitev tumorja; renal cell carcinoma; robot-assisted partial nephrectomy; robotsko asistirana delna nefrektomija; ruptura tumorja; tumor recurrence; tumor rupture; warm ischemia time